Rudimentary third arm arising from the upper back: A rare case - Adhikari, Rupendra Bahadur; Thapa, Amit; Pandey, Chakra Raj (Grande Medical Journal, 2019)
We report a case of a 2-year-old boy with rudimentary third arm arising from the dorsal spine with associated spinal dysraphism.